Integrating Augmented Reality into the FERA (Focus-Explore-Reflect-Apply) Learning Model to Improve Students’ Conceptual Understanding of Atomic Theory - Pramana, Arjuna; Rahmadani, Agung; Nurlaili, Nurlaili; Khoirunnisa, Fitriah (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to examine the effectiveness of the FERA (Focus-Explore-Reflect-Apply) learning model integrated with Augmented Reality (AR) in improving students' conceptual understanding of atomic theory. Methodology: This was a pre-experimental study employing a one-group pretest–posttest design. The sample was 32 tenth-grade students selected through cluster random sampling from ten classes in the public high school in East Kalimantan. The instruments consisted of essay-based pretest and posttest questions, teacher and student observation sheets, and AR-integrated reading materials. The data were analyzed by using descriptive statistics, normality test, Wilcoxon Signed Rank Test, normalized gain (N-Gain), and effect size (r). Main Findings: The results indicated a statistically significant improvement in students’ conceptual understanding after the intervention. The average N-Gain score was 0.67 (moderate category). Meanwhile, the effect size (r = 0.88) showed a large effect. The greatest improvement was found in the classification indicator, whereas the application indicator demonstrated relatively lower gains. Overall, the integration of FERA and AR effectively improved conceptual understanding of atomic theory. Novelty/Originality of this study: The novelty of this study lies in systematically embedding augmented reality within the structured stages of the FERA (Focus-Explore-Reflect-Apply) learning model to improve the students’ conceptual understanding of atomic theory. Unlike previous studies that often employ augmented reality as a supplementary visualization tool, this study integrated AR into a coherent pedagogical framework, aligning interactive 3D representations with specific cognitive processes in each instructional stage.